Platelet activation by Staphylococcus aureus - Loughman, Anthony J. (Trinity College (Dublin, Ireland). Department of Microbiology, 2006)
Staphylococcus aureus is the leading cause of infective endocarditis (IE). Platelet activation promoted by S. aureus resulting in aggregation and thrombus formation is thought to be an important step in the pathogenesis of IE. A detailed understanding of the molecular interactions between S. aureus and human platelets may identify targets for the development of novel therapeutic strategies to combat this often fatal infection. The fibrinogen-binding surface protein clumping factor (Clf) A is the dominant surface protein responsible for platelet aggregation by S. aureus cells in the stationary phase of growth. This study used genetically manipulated S. aureus and Lactococcus lactis strains engineered to express ClfA and a sitedirected ClfA mutant defective in fibrinogen-binding (ClfA PY). Expression of ClfA or ClfA PY from a nisin-inducible promoter in L. lactis demonstrated that a minimum level of surface expressed ClfA was required for aggregation, which is similar to the expression levels of ClfA observed in S. aureus Newman cells grown to stationary phase. A less-efficient fibrinogen-independent mechanism of platelet activation was promoted by bacteria expressing the non-fibrinogen-binding ClfA PY mutant. Using platelets that were separated from plasma, the requirement for both bound fibrinogen and immunoglobulin (Ig) G was demonstrated. Fibrinogen promoted adhesion of platelets to bacteria expressing the wild-type ClfA protein, but not to bacteria expressing the ClfA PY mutant. This adhesion was dependent on the GPIIb/IIIa integrin on resting platelets. The IgG requirement is consistent with the potent inhibition of ClfA-mediated platelet activation by a monoclonal antibody specific for the platelet low-affinity Fc receptor FcyRIIa. Furthermore the IgG had to contain antibodies specific for ClfA. A model is proposed whereby bacterial cells armed with a sufficient number of surface-bound fibrinogen molecules mediate bacterial adhesion to the low affinity platelet glycoprotein GPlIb/IIla receptor, aided by bound IgG molecules which encourages the clustering of FcyRlIa receptors. This can trigger activation leading to up-regulation of GPlIb/IIla and fibrinogen-dependent platelet aggregation. Bacteria expressing the ClfA PY mutant protein required IgG and complement assembly on the bacterial surface for interactions with platelets leading to activation.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin